Microteaching dalam Jaringan berbasis Lesson Study dan Keterampilan Penyusunan Authentic Assessment Matematika berorientasi HOTS - Erika Laras Astutiningtyas; Andhika Ayu Wulandari; Isna Farahsanti; Annisa Prima Exacta (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
The objectives of this study were to describe the implementation of microteaching in an online Lesson Study and to find out the percentage of improvement in skills in making Authentic Assessment with Higher Order Thinking Skills (HOTS) oriented through online Microteaching based on Lesson Study. This type of research is a descriptive exploratory study with a qualitative approach. The platforms used for online Microteaching courses are: Zoom, Moodle, YouTube, and the WhatsApp application. The instruments used in this study were: (1) an observation sheet on the implementation of the Lesson Study; (2) HOTS-oriented Authentic Assessment Sheet. The results of this study are: (1) The stages of Microteaching implementation in an online Lesson Study are as follows. (a) Preparation stage with the formation of a Team, (b) Implementation Phase, which includes plans, do, and see carried out online (c) Evaluation stage of activities. (2) The increase in the mean score of HOTS-oriented Authentic Assessment from Open Lesson I to Open Lesson III is 25.49%. The score category, which was in passable level, became good.